2021
DOI: 10.1007/s10238-021-00712-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of the benefit of hypomethylating agents before allogeneic hematopoietic stem cell transplantation in myelodysplastic syndromes

Abstract: Hypomethylating agents (HMAs) are effective therapies in myelodysplastic syndromes (MDS), but allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only way to cure MDS. According to the current literature, it is difficult to confirm whether HMAs bridging therapy is beneficial for MDS patients receiving allo-HSCT. Therefore, we tried to evaluate the effect of HMAs on long-term survival of the MDS patients. Databases, including PubMed, Embase Ovid, and the Cochrane Library, were searched for st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…HMAs are recommended to use for patients with HR-MDS who are not eligible for intensive treatment, resistant to immunosuppressive schemes, or as a bridging treatment before allo-HSCT. However, in the meta-analysis of Liu et al [31], they observed no differences between OS in patients with HMAs bridging to allo-HSCT and best supportive care before transplantation [hazard ratio (HR) = 0.86, 95% confidence interval (CI): 0.64-1.15, p = 0.32]. Evaluation of the effect of this therapeutic method on OS requires further prospective studies with a longer observation period.…”
Section: Hypomethylating Drugsmentioning
confidence: 99%
“…HMAs are recommended to use for patients with HR-MDS who are not eligible for intensive treatment, resistant to immunosuppressive schemes, or as a bridging treatment before allo-HSCT. However, in the meta-analysis of Liu et al [31], they observed no differences between OS in patients with HMAs bridging to allo-HSCT and best supportive care before transplantation [hazard ratio (HR) = 0.86, 95% confidence interval (CI): 0.64-1.15, p = 0.32]. Evaluation of the effect of this therapeutic method on OS requires further prospective studies with a longer observation period.…”
Section: Hypomethylating Drugsmentioning
confidence: 99%
“…A meta‐analysis of seven studies showed no survival differences between patients with MDS treated with pre allo‐HSCT HMA and those receiving pre allo‐HSCT best supportive care (HR = 0.86, 95% CI: 0.64–1.15, p = .32) 60 . However, the fact that all studies included in this meta‐analysis were retrospective and with relatively small numbers of patients raises questions about significant biases that limit the strength of the conclusions.…”
Section: Role Of Induction Treatment Before Transplantationmentioning
confidence: 99%